On Nano α∗-continuous Functions in Nano Topological Spaces - H.Mumtaj Begum, A.Gomathi, S.Maheswari (International Journal of Modern Agriculture, 2021)
This paper focuses on Nano α∗-continuous functions (Nα∗-continuous functions) in nano topological spaces and certain properties are investigated. We also investigate the concept of contra Nα∗-continuous functions and discussed their relationships with other forms of nano continuous functions. Further, we have given an appropriate examples to understand the abstract concepts clearly.